Perbandingan Routing Ulang Pada Algoritme Dijkstra dan Floyd-Warshall Dalam Mengatasi Link Failure Pada Arsitektur SDN - Risailin Dwi Jaka Fauzi; Rakhmadhany Primananda; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
There are 2 (two) types of routing, static routing and dynamic routing. Static routing is a type of routing that will done manually, while dynamic routing is a type of routing that is more automatic routing. One of network architecture that implements dynamic routing at this time is SDN, in the routing process there are several problems, one of that problem is link failure, where failure on a path can affect data sending process in the network. At this time there are many types of routing algorithms such as Dijkstra's Algorithm, Dijkstra's algorithm way to finding the shortest path by checking each path until it produces the best path. While Floyd-Warshall is more dynamic algorithm in searching for the shortest path not just fixed on the lowest cost value, but also considering the future consequences of each step that will be taken. To know about performance comparison the researcher made a comparison on the re-routing process using the Djikstra and Floyd-Warshall algorithms to find out which ones were faster in overcoming the link failure at SDN. From the comparison of the Djikstra and Floyd-Warshall algorithm's convergence time, Dijkstra's algorithm has better results i.e for scenario 1 0ms, scenario 2 16.401ms, and scenario 3 17.200ms compared to Floyd-Warshall algorithm, for scenario 1 0ms, scenario 2 19.803 ms, and scenario 3 20.401ms.